PENDAPATAN PETANI DARI SEKTOR NON PERTANIAN UNTUK MENINGKATKAN PENDAPATAN RUMAH TANGGA PETANI MISKIN DI KECAMATAN KARANGPANDAN - Mei Tri Sundari (AGRITEXTS: Journal of Agricultural Extension, 2007)
The objective of this research is to know the revenue and cost from agryculture sector and non agryculture sector in farmer family. It wants to know the condition of the farming in Karanganyar Regency. The method used in this research was analytical descriptive with survey in implementation. The location was selected purposively and it was Kecamatan Karangpandan Kabupaten Karanganyar. The data used in this research was data of 2004. The result of this research shown that revenue the peasant from sector agryculture was small. It caused the peasant also work in sector non agryculture. The average revenue the peasant from cultivation is about Rp. 2.670.692 and from sector non agryculture they get increasing revenue Rp. 1.897.616 every year.